Pengaruh Word of Mouth dan Store Image terhadap Purchase Decision Mie Gacoan di Bekasi Timur Regency - Evitha, Yuli; Praja, Dandi Fatahilah (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2024)
Culinary enthusiasts in Indonesia are increasing, especially in the field of processed noodle culinary. Indonesia itself ranks 2nd (second) in the world in the largest noodle consumer. With this, it certainly affects Mie Gacoan to develop business and innovations made to influence customer purchasing decisions. This study aims to measure the effect of word of mouth and store image on the purchase decision of Mie Gacoan in East Bekasi Regency. This study uses a quantitative method with a sample size of 100 respondents. In this study using data analysis techniques in the form of statistics with data testing using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis tests with t tests and f tests, as well as coefficient of determination tests and Pearson Correlation tests. The results of testing the regression coefficient partially obtained a tcount value on the word of mouth variable of 20.206 and the store image variable obtained a tcount of 3.003, all calculations showed greater than the ttable calculation of 1.984, which means that each independent variable partially affects the dependent variable. In the f test simultaneously obtained the results of fcount of 40.564 greater than the ftabel 3.09 so it can be concluded that word of mouth and store image have a significant influence on purchase decisions.